Pengaruh Motivasi Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan Perusahaan Terbatas Sinarmas Medan Sumatera Utara - Rizki Rahmawani; Hery Syahrial (Universitas Medan Area, 2021)
This study aims to determine whether job motivation and job satisfaction have a significant positive effect partially or simultaneously on the performance of employees of PT. Sinarmas Medan. This research was conducted by distributing questionnaires to 136 people. This type of research is a quantitative descriptive study with the sampling technique in this study is stratified random sampling. The data analysis technique in this study uses multiple linear regression analysis techniques. The results obtained from this study are job motivation and job satisfaction have a significant positive effect partially and simultaneously on the performance of employees of PT. Sinarmas Medan.